Interleukin 6 receptor inhibition in primary Sjögren syndrome: a multicentre double-blind randomised placebo-controlled trial. Issue 3 (18th November 2020) - Felten, Renaud; Devauchelle-Pensec, Valérie; Seror, Raphaèle; Duffau, Pierre; Saadoun, David; Hachulla, Eric; Pierre Yves, Hatron; Salliot, Carine; Perdriger, Aleth; Morel, Jacques; Mékinian, Arsène; Vittecoq, Olivier; et al.
Abstract : Objectives: No immunomodulatory drug has been approved for primary Sjögren's syndrome, a systemic autoimmune disease affecting 0.1% of the population. To demonstrate the efficacy of targeting interleukin 6 receptor in patients with Sjögren's syndrome-related systemic complications. Methods: Multicentre double-blind randomised placebo-controlled trial between 24 July 2013 and 16 July 2018, with a follow-up of 44 weeks, involving 17 referral centres. Inclusion criteria were primary Sjögren's syndrome according to American European Consensus Group criteria and score ≥5 for the EULAR Sjögren's Syndrome Disease activity Index (ESSDAI, score of systemic complications). Patients were randomised to receive either 6 monthly infusions of tocilizumab or placebo. The primary endpoint was response to treatment at week 24. Response to treatment was defined by the combination of (1) a decrease of at least 3 points in the ESSDAI, (2) no occurrence of moderate or severe activity in any new domain of the ESSDAI and (3) lack of worsening in physician's global assessment on a Visual Numeric Scale ≥1/10, all as compared with enrolment. Results: 110 patients were randomised, 55 patients to tocilizumab (mean (SD) age: 50.9 (12.4) years; women: 98.2%) and 55 patients to placebo (54.8 (10.7) years; 90.9%). At 24 weeks, the proportion of patients meeting the primary endpoint was 52.7% (29/55) in the tocilizumab group and 63.6% (35/55) in the placebo group, for a difference of −11.4% (95% credible interval −30.6 to 9.0) (Pr[Toc >Pla]=0.14). Conclusion: Among patients with primary Sjögren's syndrome, the use of tocilizumab did not improve systemic involvement and symptoms over 24 weeks of treatment compared with placebo. Trial registration number: NCT01782235 .